2018
DOI: 10.37358/rc.18.7.6384
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and removal of Direct Red 28 diazo dye in living polymeric systems

Abstract: Aquatic environments are often contaminated with various compounds, with potential toxicity towards aquatic organisms, which may enter the food chain. Azo dyes are used in various industries and contamination of waters has been reported. The present paper assesses the toxicity of the synthetic, water soluble Congo Red dye towards Lemna minor from a physiological and cytogenetical point of view. The dye was tested in 5-5000 ppm concentrations. Total frond surface, root growth and fresh mass reductions were regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Hellophytes (Phragmites australis, Alternanthera philoxeroides, Typha domingensis, Junus sp. ), ornamental plants (Ipomoea hederifolia, Aster amellus, Portulaca grandiflora, Zinnia angustifolia, Petunia grandiflora, Glandularia pulchella) and many ferns and herbs have been extensively used for dye removal. ,, Recently, aquatic plants such as Pistia stratiotes or Lemna minor have been used successfully in the elimination of carcinogenic azo red dye, although plants cannot be reused and at high concentrations suffer irreversible damage. , Some of these plants have been used in phytoreactors and constructed wetlands, obtaining interesting results in biotransformation, although the derived products were not always non/less toxic than untreated compounds. , Plant tissue cultures can be an alternative for the degradation of these compounds. They offer advantages like they lack chlorophyll and other plant pigments, reproducibility, homogeneity of the plant material, reduced problems of uptake and transport, easy manipulation and more quick results.…”
Section: H Bonded Semiconductors and Their Suitability For Biodegrada...mentioning
confidence: 99%
See 1 more Smart Citation
“…Hellophytes (Phragmites australis, Alternanthera philoxeroides, Typha domingensis, Junus sp. ), ornamental plants (Ipomoea hederifolia, Aster amellus, Portulaca grandiflora, Zinnia angustifolia, Petunia grandiflora, Glandularia pulchella) and many ferns and herbs have been extensively used for dye removal. ,, Recently, aquatic plants such as Pistia stratiotes or Lemna minor have been used successfully in the elimination of carcinogenic azo red dye, although plants cannot be reused and at high concentrations suffer irreversible damage. , Some of these plants have been used in phytoreactors and constructed wetlands, obtaining interesting results in biotransformation, although the derived products were not always non/less toxic than untreated compounds. , Plant tissue cultures can be an alternative for the degradation of these compounds. They offer advantages like they lack chlorophyll and other plant pigments, reproducibility, homogeneity of the plant material, reduced problems of uptake and transport, easy manipulation and more quick results.…”
Section: H Bonded Semiconductors and Their Suitability For Biodegrada...mentioning
confidence: 99%
“…164,165 Some of these plants have been used in phytoreactors and constructed wetlands, obtaining interesting results in biotransformation, although the derived products were not always non/less toxic than untreated compounds. 159,166 Plant tissue cultures can be an alternative for the degradation of these compounds. They offer advantages like they lack chlorophyll and other plant pigments, reproducibility, homogeneity of the plant material, reduced problems of uptake and transport, easy manipulation and more quick results.…”
Section: H Bonded Semiconductors and Theirmentioning
confidence: 99%
“…A similar study was conducted by Lade et al (2015) on the degraded metabolites of dye RB172 through acute and phytotoxicity, and the same findings were reported. Lobiuc et al (2018) assessed CR toxicity towards Lemna minor and reported reduction in root growth, total frond surface and fresh mass reduced from 5 ppm dye concentration, whereas above 2500 ppm concentration, complete plant growth was inhibited. Khandare et al (2013) demonstrated the metabolism fate of Direct Red 5B by P. grandiflora, P. putida, and their consortium with the help of GC-MS analysis.…”
Section: Impact Of Azo Dye Contamination On Flora and Faunamentioning
confidence: 99%
“…Most of those wastewaters have been evacuated into lakes and rivers, leading to eutrophication of aquatic systems [12]. Anthropogenic activities, especially chemical pollution, have triggered various forms of environmental change [13]. According to the OECD (World Economic Cooperation and Development Organization), 80% of water eutrophication has been attributed to phosphorus, 10% of water bodies eutrophication directly related to nitrogen and phosphorus and the remaining 10% has been triggered by nitrogen and other factors [14].…”
mentioning
confidence: 99%